Jews and the Arab world : intertwined legacies - Duncan Hart, Ron 1941- (Institute for Tolerance Studies, 2020)
"For 1,400 years Jews and Arabs have lived side by side and mostly with mutual respect. The oldest center of Jewish life outside of Israel was Baghdad. The greatest Jewish scholars lived there and prepared the "Babylonian" Talmud. In Western Europe, a major center of Jewish life was the 800 years under Muslim rule in Spain. When the Muslims were driven out of Spain in 1492, Jews were expelled from that country three months later, mostly joining the Muslim retreat into North Africa and the Ottoman Empire. The Jewish/Arab conflict that started in the twentieth century is an anomaly, and this book analyzes the issues that transformed that long history of co-existence into the conflict of today, including the four stages of the current conflict and the new developments that have occurred in recent years"--